Vertical resonator-type light-emitting element and method for manufacturing same
Patent Information
- Application Number
- CN202380047490.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-06-07
- Publication Date
- 2025-02-07
Smart Images

Figure CN119404395A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a vertical cavity light emitting element using a semiconductor multilayer film reflector, and in particular to a vertical cavity semiconductor light emitting element such as a vertical cavity surface emitting laser (VCSEL). The present invention also relates to a method for manufacturing the vertical cavity light emitting element. Background Art
[0002] A vertical cavity light emitting element having distributed Bragg reflectors (DBR) disposed above and below an active layer is known. In a semiconductor light emitting element, an electron blocking layer having a band gap energy higher than that of an active layer is used to prevent overflow of electron carriers.
[0003] For example, Patent Document 1 discloses a vertical cavity light-emitting element composed of a GaN-based semiconductor, which includes an AlGaN layer as an electron blocking layer between an active layer and a p-type semiconductor mesa structure. In addition, Patent Document 1 discloses that the band gap energy is increased by increasing the Al component of the electron blocking layer.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 6966843 Summary of the invention
[0007] Technical issues
[0008] For example, in the above-mentioned vertical cavity light-emitting element, when the p-type dopant concentration in the p-type AlGaN layer increases, the concentration of hole carriers increases, resulting in a higher carrier injection efficiency. However, if the concentration of the p-type dopant increases too much, there is a problem that the element life may be reduced due to the diffusion of the p-type dopant into the active layer and the diffusion of defects in the active layer caused by the high concentration of the p-type dopant.
[0009] The present invention is made in view of the above problems, and its object is to provide a vertical cavity light emitting element with high life span and high efficiency while having high carrier injection efficiency and suppressing the decrease of element life span, and a method for manufacturing the same.
[0010] Technical Solution
[0011] The vertical cavity light-emitting element of the present invention comprises a substrate, a first multilayer film reflector, an n-type nitride semiconductor layer, an active layer, a p-type AlGaN layer, a p-type nitride semiconductor layer and a second multilayer film reflector. In the first multilayer film reflector as a semiconductor multilayer film, two semiconductor layers with different refractive indices are alternately formed multiple times on the substrate. The n-type nitride semiconductor layer is formed on the first multilayer film reflector and is made of a nitride semiconductor containing an n-type dopant. The active layer is formed on the n-type nitride semiconductor layer. The p-type AlGaN layer is formed on the active layer and contains Mg as a p-type dopant. The p-type AlGaN layer has a structure in which three or more AlGaN layers with different Al components are stacked. The p-type nitride semiconductor layer is formed on the p-type AlGaN layer. The p-type nitride semiconductor layer is a semiconductor layer made of a nitride semiconductor containing a p-type dopant. The second multilayer film reflector is formed on the p-type nitride semiconductor layer and is arranged at a position opposite to the first multilayer film reflector. In an Al composition curve indicating a change in the Al composition in the p-type AlGaN layer in a layer thickness direction and an Mg concentration curve indicating a change in the Mg concentration in the p-type AlGaN layer in a layer thickness direction, which are analyzed by secondary ion mass spectrometry (SIMS) of a p-type AlGaN layer, when a width range at 50% of a peak value of the Al composition curve is defined as the p-type AlGaN layer, and the p-type AlGaN layer is divided into a first region having a layer thickness of 1 / 10 of the p-type AlGaN layer, a second region having a layer thickness of 2 / 5 of the p-type AlGaN layer, and a third region having a layer thickness of 1 / 2 of the p-type AlGaN layer in sequence from the active layer side in a layer thickness direction, the magnitude relationship between the Al components indicated by the Al composition curve in each region is first region < third region < second region, and the Mg concentration indicated by the Mg concentration curve is less than 3×10 19 atoms / cm 3 , and the relationship between the Mg concentrations in the various regions is that the first region < the second region < the third region, and the Mg concentration in at least a portion of the second region is 3×10 18 atoms / cm 3 or above, and the Mg concentration curve has a peak in the second region.
[0012] The vertical cavity light-emitting element according to the present invention comprises a substrate, a first multilayer film reflector, an n-type nitride semiconductor layer, an active layer, a p-type AlGaN layer, a p-type nitride semiconductor layer and a second multilayer film reflector. The first multilayer film reflector is a semiconductor layer in which two semiconductor layers with mutually different refractive indices are alternately stacked multiple times on the substrate. The n-type nitride semiconductor layer is formed on the first multilayer film reflector and is made of a nitride semiconductor containing an n-type dopant. The active layer is formed on the n-type nitride semiconductor layer. The p-type AlGaN layer is formed on the active layer and contains Mg as a p-type dopant. The p-type AlGaN layer has a structure in which three or more AlGaN layers with different Al components are stacked. The p-type nitride semiconductor layer is formed on the p-type AlGaN layer. The p-type nitride semiconductor layer is a semiconductor layer composed of a nitride semiconductor containing a p-type dopant. The second multilayer film reflector is formed on the p-type nitride semiconductor layer and is arranged at a position opposite to the first multilayer film reflector. In an Al composition curve indicating a change in the Al composition in the p-type AlGaN layer in a layer thickness direction and an Mg concentration curve indicating a change in the Mg concentration in the p-type AlGaN layer in a layer thickness direction, which are analyzed by secondary ion mass spectrometry (SIMS) of a p-type AlGaN layer, when a width range at 50% of a peak value of the Al composition curve is defined as a p-type AlGaN layer, and the p-type AlGaN layer is divided into a first region having a layer thickness of 1 / 10 of the p-type AlGaN layer, a second region having a layer thickness of 2 / 5 of the p-type AlGaN layer, and a third region having a layer thickness of 1 / 2 of the p-type AlGaN layer in sequence from the active layer side in the layer thickness direction, the magnitude relationship between the Al components indicated by the Al composition curve in each region is: first region < third region < second region, and the Mg concentration indicated by the Mg concentration curve is less than 3×10 19 atoms / cm 3 , and the relationship between the Mg concentrations in each region is the first region < the second region < the third region. The average Mg concentration in the second region is 3×10 18 atoms / cm 3 As above, and the Mg concentration curve in the second region is configured so that the average value of the absolute value of the slope in the portion on the third region side relative to the center of the second region in the layer thickness direction in the second region is smaller than the average value of the absolute value of the slope in the portion on the first region side.
[0013] According to the present invention, the manufacturing method of a vertical cavity light-emitting element by metal organic chemical vapor deposition (MOCVD) includes: a step of forming a first multilayer film reflector by alternately growing two semiconductor layers having different refractive indices on a substrate; an n-type nitride semiconductor layer growth step, growing an n-type nitride semiconductor layer on the first multilayer film reflector while supplying a material gas of an n-type dopant; a step of forming an active layer on the n-type nitride semiconductor layer; a p-type AlGaN layer growth step, growing a p-type AlGaN layer as an AlGaN layer having a p-type conductivity type on the active layer while supplying a material gas of Mg as a p-type dopant; a p-type nitride semiconductor layer growth step, growing a p-type nitride semiconductor layer on the p-type AlGaN layer; and a step of forming a second multilayer film reflector on the p-type nitride semiconductor layer opposite to the first multilayer film reflector. The p-type AlGaN layer growth step includes: a first growth step, while raising the growth temperature from a first temperature to a second temperature, supplying a nitrogen source gas and a Ga material gas in predetermined supply amounts, supplying an Al material gas in a first supply amount, and supplying the Mg material gas in a second supply amount to grow a first p-type AlGaN layer; a second growth step, after the first growth step, growing a second p-type AlGaN layer while maintaining the supply amounts of the nitrogen source gas, the Ga material gas, the Al material gas, and the Mg material gas used in the first growth step; and a third growth step, after the second growth step, growing a third p-type AlGaN layer while supplying the Al material gas in a third supply amount lower than the first supply amount and supplying the Mg material gas in a fourth supply amount lower than the second supply amount.
[0014] The present invention provides a method for manufacturing a vertical cavity light-emitting element by metal organic chemical vapor deposition (MOCVD) including: a step of forming a first multilayer film reflector by alternately growing two semiconductor layers having different refractive indices on a substrate; an n-type nitride semiconductor layer growth step of growing an n-type nitride semiconductor layer on the first multilayer film reflector while supplying a material gas of an n-type dopant; a step of forming an active layer on the n-type nitride semiconductor layer; a p-type AlGaN layer growth step of growing a p-type AlGaN layer as an AlGaN layer having a p-type conductivity type on the active layer while supplying a material gas of Mg as a p-type dopant; a p-type nitride semiconductor layer growth step of growing a p-type nitride semiconductor layer on the p-type AlGaN layer; and a step of forming a second multilayer film reflector on the p-type nitride semiconductor layer opposite to the first multilayer film reflector. The p-type AlGaN layer growth step includes: a pretreatment step, supplying a nitrogen source gas at a predetermined supply amount and supplying a Mg material gas at a first supply amount while raising the growth temperature from a first temperature to a second temperature; a first growth step, after the pretreatment step, growing a first p-type AlGaN layer by supplying a Ga material gas at a predetermined supply amount, supplying an Al material gas at a second supply amount, and supplying a Mg material gas at a third supply amount while continuing to supply the nitrogen source gas; a second growth step, after the first growth step, growing a second p-type AlGaN layer while maintaining the supply amounts of the nitrogen source gas, the Ga material gas, the Al material gas, and the Mg material gas used in the first growth step; and a third growth step, after the second growth step, growing a third p-type AlGaN layer while supplying the Al material gas at a fourth supply amount lower than the second supply amount and supplying the Mg material gas at a fifth supply amount lower than the third supply amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a perspective view showing the structure of a surface emitting laser according to Embodiment 1.
[0016] Figure 2 is a plan view showing the structure of the surface emitting laser according to Embodiment 1.
[0017] Figure 3 is a cross-sectional view showing the structure of a surface emitting laser according to Embodiment 1.
[0018] Figure 4 : is a graph showing the results of SIMS analysis of the p-type AlGaN layer of the surface emitting laser according to Embodiment 1.
[0019] Figure 5 This is a flowchart showing an outline of a manufacturing process of the surface emitting laser according to the first embodiment.
[0020] Figure 6 1 is a diagram schematically showing the growth sequence of a p-type AlGaN layer of the surface emitting laser according to Embodiment 1.
[0021] Figure 7 is a diagram showing the results of SIMS analysis of a p-type AlGaN layer of a surface emitting laser according to a comparative example.
[0022] Figure 8 is a diagram showing the results of SIMS analysis of a p-type AlGaN layer of a surface emitting laser according to a comparative example.
[0023] Fig. 9 : is a graph showing the results of SIMS analysis of the p-type AlGaN layer of the surface emitting laser according to the second embodiment.
[0024] Fig.10 FIG. 1 is a diagram showing the results of SIMS analysis of a p-type AlGaN layer of a surface emitting laser according to a modification of the second embodiment.
[0025] Fig.11 1 is a diagram schematically showing the growth sequence of a p-type AlGaN layer of a surface emitting laser according to a modification of the second embodiment.
[0026] Fig.12 FIG. 1 is a diagram showing the results of SIMS analysis of a p-type AlGaN layer of a surface emitting laser according to another modification of the second embodiment.
[0027] Fig.13 FIG. 1 is a diagram showing the results of SIMS analysis of a p-type AlGaN layer of a surface emitting laser according to another modification of the second embodiment.
[0028] Fig.14 is a cross-sectional view showing the structure of a surface emitting laser according to Embodiment 3.
[0029] Fig.15 : is a graph showing the results of SIMS analysis of the p-type AlGaN layer of the surface emitting laser according to the third embodiment.
[0030] Fig.16 Schematically showing the growth sequence of the p-type AlGaN layer of the surface emitting laser according to Embodiment 3. DETAILED DESCRIPTION
[0031] The preferred embodiments of the present invention are described below, but these embodiments may be appropriately changed and combined. In the following description and drawings, the same reference numerals are used to describe substantially the same or equivalent components.
[0032] Implementation Method 1
[0033] The structure of a vertical cavity surface emitting laser (VCSEL, hereinafter also referred to as a surface emitting laser) 10 according to Embodiment 1 of the present invention will be described with reference to the drawings. The surface emitting laser 10 of Embodiment 1 is composed of a nitride-based semiconductor layer.
[0034] Figure 1 1 is a perspective view schematically showing the structure of the surface emitting laser 10 .
[0035] The substrate 11 is a substrate for growing a nitride semiconductor layer constituting the surface emitting laser 10. For example, the substrate 11 has a rectangular top surface shape. In the present embodiment, the substrate 11 is a GaN substrate. The top surface of the substrate 11, that is, the surface on which the nitride semiconductor layer is grown, is preferably a C-plane or a surface that deviates from the C-plane by less than 1°. In addition to the GaN substrate, a substrate such as a sapphire substrate and an AlN substrate can also be used as the substrate 11.
[0036] The underlayer 13 is formed on the substrate 11. The underlayer 13 is an undoped GaN layer and functions as a buffer layer for improving the crystallinity of the nitride semiconductor layer grown on the underlayer 13.
[0037] The first multilayer film reflector 15 is formed on the bottom layer 13. The first multilayer film reflector 15 is a semiconductor multilayer film reflector in which a low refractive index semiconductor film having a component of AlInN and a high refractive index semiconductor film having a GaN component having a higher refractive index than the low refractive index semiconductor film are alternately stacked. The first multilayer film reflector 15 is a distributed Bragg reflector (DBR) composed of a nitride semiconductor material. In other words, the first multilayer film reflector 15 is a nitride semiconductor multilayer film reflector.
[0038] The n-type semiconductor layer 17 is an n-type GaN layer formed on the first multilayer film reflecting mirror 15. The n-type semiconductor layer 17 is doped with Si as an n-type impurity.
[0039] The n-type semiconductor layer 17 includes a prism-shaped lower portion 17A and a cylindrical upper portion 17B disposed on the lower portion 17A. In other words, the n-type semiconductor layer 17 includes a cylindrical upper portion 17B protruding from the top surface of the prism-shaped lower portion 17A. In other words, the n-type semiconductor layer 17 has a mesa-shaped structure including the upper portion 17B. The n-type semiconductor layer 17 includes an exposed portion 17E in which the top surface of the lower portion 17A is partially exposed.
[0040] The active layer 19 is formed on the upper portion 17B of the n-type semiconductor layer 17. The active layer 19 is a light emitting structure layer composed of a plurality of semiconductor layers forming a multi-quantum well (MQW) structure, for example. Specifically, the active layer 19 is a layer having a quantum well structure including a well layer having an InGaN component and a barrier layer having a GaN component. When current is injected into the surface emitting laser 10, light is generated in the active layer 19.
[0041] The intermediate layer 21 is an undoped GaN layer formed on the active layer 19. The intermediate layer 21 has a buffer layer function of increasing the distance between the active layer 19 and the p-type semiconductor layer 23 formed on the intermediate layer 21, so as to suppress the diffusion of impurities from the p-type semiconductor layer 23 formed on the intermediate layer 21 to the active layer 19.
[0042] As described above, the p-type semiconductor layer 23 is formed on the intermediate layer 21 and is a layer including a plurality of semiconductor layers doped with p-type impurities. Mg is doped as the p-type impurity.
[0043] The n-electrode 25 is a metal electrode provided on the exposed portion 17E of the n-type semiconductor layer 17. The n-electrode 25 is electrically connected to the n-type semiconductor layer 17. For example, the n-electrode 25 is formed in a ring shape surrounding the upper portion 17B of the n-type semiconductor layer 17. The shape of the n-electrode 25 is not limited thereto, and the n-electrode 25 may also be an electrode layer formed in a layered shape over the entire surface of the exposed portion 17E.
[0044] The insulating layer 27 is a layer formed on the p-type semiconductor layer 23 and made of an insulator or a material having lower conductivity than the p-type semiconductor layer 23. The insulating layer 27 is made of a substance such as SiO2 having a lower refractive index than the material constituting the p-type semiconductor layer 23. The insulating layer 27 is formed in a ring shape on the p-type semiconductor layer 23 and has an opening (not shown) in the center portion for exposing the p-type semiconductor layer 23.
[0045] The semi-transparent electrode 29 is formed on the insulating layer 27. The semi-transparent electrode 29 is also formed on the p-type semiconductor layer 23 through the opening of the insulating layer 27 and is electrically connected to the p-type semiconductor layer 23. The semi-transparent electrode 29 is formed using a metal oxide (for example, ITO or IZO) that is semi-transparent to light emitted from the active layer 19.
[0046] The second multilayer film reflector 31 is a dielectric multilayer film provided on the semi-transparent electrode 29 on the opening of the insulating layer 27. The second multilayer film reflector 31 is a dielectric multilayer film reflector composed of two dielectric films having different refractive indices (e.g., niobium oxide (Nb2O5) and silicon oxide (SiO2)) alternately stacked.
[0047] The p-electrode 33 is a metal electrode provided on the semi-transparent electrode 29. The p-electrode 33 is electrically connected to the semi-transparent electrode 29. The p-electrode 33 is formed in a ring shape surrounding the second multi-layer film reflecting mirror 31.
[0048] Figure 2 is a top view of the surface emitting laser 10. As described above, the surface emitting laser 10 includes the n-type semiconductor layer 17 which is formed on the substrate 11 having a rectangular top surface shape and has a mesa-shaped structure.
[0049] The ring-shaped n-electrode 25 is formed on the exposed portion 17E exposed from the mesa-shaped portion of the n-type semiconductor layer 17 so as to surround the mesa-shaped portion.
[0050] As described above, the surface emitting laser 10 includes the active layer 19, the intermediate layer 21, the p-type semiconductor layer 23, and the ring-shaped insulating layer 27 (in Figure 2 The active layer 19, the intermediate layer 21, the p-type semiconductor layer 23 and the ring-shaped insulating layer 27 are sequentially formed on the upper portion 17B of the mesa-shaped portion of the n-type semiconductor layer 17 and have a circular top surface shape. The insulating layer 27 has an opening OP.
[0051] The semi-transparent electrode 29 is formed on the insulating layer 27 to cover the opening OP of the insulating layer 27. The second multi-layer film reflecting mirror 31 is provided on the semi-transparent electrode 29 in a region including the center CA of the semi-transparent electrode 29.
[0052] The second multilayer film reflecting mirror 31 is formed to cover the opening OP in a plan view. The second multilayer film reflecting mirror 31 may also be formed to overlap the opening OP in a plan view.
[0053] Furthermore, a ring-shaped p-electrode 33 is provided around the periphery of the semi-transparent electrode 29 .
[0054] Figure 3 is the edge of the surface emitting laser 10 Figure 2 3-3 line cross-sectional view. As described above, the p-type semiconductor layer 23 is composed of a plurality of semiconductor layers containing p-type impurities. The structure of the p-type semiconductor layer 23 is described below.
[0055] The p-type AlGaN layer 35 is formed on the intermediate layer 21 and is doped with Mg as a p-type impurity. The p-type AlGaN layer 35 functions as an electron blocking layer.
[0056] The p-type AlGaN layer 35 is composed of three p-type AlGaN layers having different Mg concentration distributions and Al composition distributions. Figure 3 In FIG. 4 , three layers constituting the p-type AlGaN layer 35 are shown as a first layer 37 , a second layer 39 , and a third layer 41 .
[0057] In the surface emitting laser 10, it is important to suppress the threshold current density to be low by efficiently injecting electron carriers and hole carriers into the active layer 19 and keeping them in the active layer 19. If the overflow of electron carriers occurs, the threshold current density increases, and not only the current utilization efficiency is reduced, but also the element is degraded due to the influence of heat emitted by carriers that do not contribute to light emission, resulting in a shortened element life.
[0058] By doping Mg into the p-type AlGaN layer 35 serving as an electron blocking layer, the hole carrier concentration of the p-type AlGaN layer 35 increases and the Fermi level decreases. This suppresses carrier overflow and improves carrier injection efficiency, thereby suppressing an increase in the threshold current density of the surface emitting laser 10.
[0059] On the other hand, if the Mg concentration in the p-type AlGaN layer 35 is too high, the device life may be reduced due to Mg diffusion into the active layer or defects caused by Mg extending to the active layer.
[0060] The inventors of the present application have found that it is important to precisely control the concentration distribution of Mg in the p-type AlGaN layer 35 in the layer thickness direction in order to improve the carrier injection efficiency while suppressing the reduction in device life due to Mg in the p-type AlGaN layer 35 .
[0061] In the present invention, in the first layer 37 closest to the active layer 19, the Mg concentration is controlled so as not to become too high, and in the second layer 39 adjacent to the first layer 37 and the third layer 41 farthest from the active layer, the Mg concentration and the Al component are controlled so that the Mg concentration and the Mg concentration distribution are suitable for improving the carrier injection efficiency.
[0062] As described above, the intermediate layer 21 is provided between the active layer 19 and the p-type semiconductor layer 23. The intermediate layer 21 has a function of increasing the distance between the p-type semiconductor layer 23 and the active layer 19 and suppressing the diffusion of p-type impurities into the active layer 19 and / or the influence of defects caused by p-type impurities. For example, the intermediate layer 21 is formed to have a layer thickness of 30 nm to 145 nm. For example, the surface emitting laser 10 may also be configured without the intermediate layer 21.
[0063] The p-type nitride semiconductor layer 43 is formed on the p-type AlGaN layer 35 and is a nitride semiconductor layer doped with a p-type impurity. For example, the p-type nitride semiconductor layer 43 is a GaN layer doped with Mg as a p-type impurity.
[0064] The p-type contact layer 45 is formed on the p-type nitride semiconductor layer 43 and is a nitride semiconductor layer doped with p-type impurities at a higher concentration than the p-type nitride semiconductor layer 43. The p-type contact layer 45 is, for example, a GaN layer doped with Mg as a p-type impurity at a higher concentration than the p-type nitride semiconductor layer 43.
[0065] Therefore, the p-type semiconductor layer 23 is constituted by stacking the p-type AlGaN layer 35 , the p-type nitride semiconductor layer 43 , and the p-type contact layer 45 in this order.
[0066] The insulating layer 27 is formed on the p-type contact layer 45. As described above, the semi-transparent electrode 29 is formed on the insulating layer 27 to cover the opening OP of the insulating layer 27, and the semi-transparent electrode 29 contacts the p-type contact layer 45 through the opening OP.
[0067] The p-electrode 33 is in electrical contact with the semi-transparent electrode 29 . Therefore, the p-electrode 33 is electrically connected to the p-type semiconductor layer 23 via the semi-transparent electrode 29 .
[0068] In the surface emitting laser 10, current is injected into the p-type semiconductor layer 23 only from the portion exposed through the opening OP of the insulating layer 27. Therefore, the opening OP serves as a current confinement structure that limits the current supply range to the active layer 19.
[0069] In the surface emitting laser 10, the first multilayer film reflecting mirror 15 and the second multilayer film reflecting mirror 31 are arranged opposite to each other. The first multilayer film reflecting mirror 15 has a slightly lower reflectivity than the second multilayer film reflecting mirror 31. Therefore, a part of the light emitted from the active layer 19 and resonated between the first multilayer film reflecting mirror 15 and the second multilayer film reflecting mirror 31 passes through the first multilayer film reflecting mirror 15 and the substrate 11 and is extracted to the outside.
[0070] Figure 4 The results of SIMS analysis of the p-type AlGaN layer 35 of the surface emitting laser 10 according to Embodiment 1 are shown. Figure 4 The Al component distribution and Mg concentration distribution in the depth direction (i.e., layer thickness direction) from the p-type nitride semiconductor layer 43 which is an upper layer of the p-type AlGaN layer 35 toward the intermediate layer 21 which is a lower layer of the p-type AlGaN layer 35 (i.e., from the surface side toward the active layer side (substrate 11 side)) are shown.
[0071] exist Figure 4 In FIG. 1 , the horizontal axis represents the layer thickness from the surface side toward the active layer side, that is, the depth (nm), the major axis represents the Mg concentration, and the minor axis represents the Al composition. Figure 4 In FIG. 1 , the Al composition curve showing the change of the Al composition in the depth direction is indicated by a dotted line. Figure 4 In FIG. 1 , a Mg concentration curve showing the change in Mg concentration in the depth direction is represented by a solid line.
[0072] for Figure 4 The Al composition curve shown defines the range of the width at 50% of the maximum peak of the Al composition (i.e., the entire width at half the maximum value) as the p-type AlGaN layer 35. In this embodiment, the p-type AlGaN layer defined on the Al composition curve is divided into three regions in the layer thickness direction. Specifically, the p-type AlGaN layer 35 is divided in the layer thickness direction from the active layer side toward the surface side: a region with a layer thickness of one-tenth (10%) as the first region AR1, a region with a layer thickness of two-fifths (40%) as the second region AR2, and a region with a layer thickness of one-half (50%) as the third region AR3, and the Al composition and Mg concentration are described.
[0073] Therefore, when focusing on Figure 4 When the horizontal axis of the layer thickness is represented in the curve graph shown, the entire width at half of the above-mentioned maximum value corresponds to the total layer thickness of the p-type AlGaN layer 35, and on the horizontal axis, the first area AR1 corresponds to one-tenth of the layer thickness portion of the p-type AlGaN layer 35, the second area AR2 corresponds to two-fifths of the layer thickness portion, and the third area AR3 corresponds to one-half of the layer thickness portion.
[0074] [Mg concentration curve]
[0075] First, the Mg concentration indicated by the Mg concentration curve and the distribution of the Mg concentration in the layer thickness direction are described.
[0076] like Figure 4 As shown in the Mg concentration curve, the Mg concentration in the entire layer thickness of the p-type AlGaN layer 35 is less than 1×10 19 atoms / cm 3 By keeping the Mg concentration less than 1×10 19 atoms / cm 3 , thereby preventing the diffusion of Mg into the active layer and the extension of defects caused by Mg into the active layer. This suppresses the reduction of element life caused by high concentration of Mg.
[0077] When the peak concentration of Mg in the p-type AlGaN layer 35 reaches 3×10 19 atoms / cm 3 In the above case, the presence of a large amount of Mg improves the carrier injection efficiency, but Mg easily diffuses into the active layer and defects caused by Mg tend to spread to the active layer, so the device life tends to be reduced.
[0078] Therefore, by controlling the Mg concentration in the p-type AlGaN layer 35 to less than 3×10 19 atoms / cm3 , more preferably less than 1×10 19 atoms / cm 3 , it is possible to suppress the reduction in device life caused by such a high concentration of Mg.
[0079] In this embodiment, in order to suppress the reduction of the device life due to the high concentration of Mg, the Mg concentration is controlled to be less than 1×10 19 atoms / cm 3 .
[0080] In addition, among the regions in the layer thickness direction of the p-type AlGaN layer 35, the closer the distance to the active layer 19, the easier it is for Mg to diffuse into the active layer 19, and the easier it is for defects caused by Mg to extend to the active layer. In view of these circumstances, it is preferred that the first region AR1 closest to the active layer 19 has the lowest Mg concentration, and the third region AR3 farthest from the active layer 19 has the highest Mg concentration.
[0081] like Figure 4 As shown, in this embodiment, when the average value of the Mg concentration in each region shown by the Mg concentration curve is compared between the regions, the third region AR3 is the largest, the second region AR2 is the second largest, and the first region AR1 is the smallest (the first region AR1<the second region AR2<the third region AR3). Therefore, by making the Mg concentration of the first region AR1 closest to the active layer 19 the lowest, the diffusion of Mg into the active layer and the extension of defects caused by Mg into the active layer are suppressed, and the reduction of the element life caused by the high concentration of Mg is suppressed.
[0082] From the perspective of suppressing the reduction in device life due to such high Mg concentration, the Mg concentration in the first region is preferably less than 2×10 18 atoms / cm 3 .
[0083] Furthermore, in order to ensure sufficient carrier injection efficiency in the surface emitting laser 10, it is necessary that the Mg concentration in the second region is not too low, and one of the indicators is that the Mg concentration in at least a part of the second region AR2 is 3×10 18 atoms / cm 3 Furthermore, the distribution of the Mg concentration in the second region AR2 is also important, and it is known that when the Mg concentration curve has a peak in the second region AR2, sufficient carrier injection efficiency can be ensured.
[0084] like Figure 4 As shown, in this embodiment, the Mg concentration indicated by the Mg concentration curve is 3×10 18atoms / cm 3 The above, and the Mg concentration curve has a peak in the second region. By controlling the Mg concentration in this way, sufficient carrier injection efficiency is ensured, and thus an increase in the threshold current density is suppressed.
[0085] [Al composition curve]
[0086] Figure 4 The Al composition curve shown has a peak in the second region AR2. More specifically, when the average values of the Al composition in each region shown by the Al composition curve are compared between the regions, the second region AR2 has the largest value, the third region AR3 has the second largest value, and the first region AR1 has the smallest value (first region AR1<third region AR3<second region AR2).
[0087] Increasing the Al composition in the region with a low Mg concentration increases the threshold voltage. Therefore, in the first region AR1 where the Mg concentration is low, the Al composition is also reduced to suppress an increase in the threshold voltage.
[0088] Furthermore, by making the Al composition of the second region AR2 the highest, it is possible to increase the blocking potential and suppress the overflow of electron carriers.
[0089] Furthermore, by making the Al composition of only the second region AR2 the highest without increasing the Al composition of the entire p-type AlGaN layer, it is possible to suppress the generation of cracks due to lattice mismatch between the Al-rich layer and the adjacent GaN layer.
[0090] As described above, the surface emitting laser 10 of embodiment 1 is constructed to include: a first multilayer film reflector stacked on a substrate; an n-type nitride semiconductor layer formed on the first multilayer film reflector; an active layer formed on the n-type nitride semiconductor layer; a p-type AlGaN layer formed on the active layer, containing Mg as a p-type dopant and having a structure in which three AlGaN layers with different Al compositions are stacked; a p-type nitride semiconductor layer formed on the p-type AlGaN layer; and a second multilayer film reflector formed on the p-type semiconductor layer and arranged in a position opposite to the first multilayer film reflector.
[0091] For the p-type AlGaN layer of embodiment 1, it is assumed that in an Al composition curve representing the change of the Al component in the p-type AlGaN layer in the layer thickness direction and a Mg concentration curve representing the change of the Mg concentration in the p-type AlGaN layer in the layer thickness direction analyzed by secondary ion mass spectrometry (SIMS) of the p-type AlGaN layer, the width range at 50% of the peak value of the Al composition curve is defined as the p-type AlGaN layer, and the p-type AlGaN layer is divided from the active layer side into a first region having a layer thickness of 1 / 10 of the p-type AlGaN layer, a second region having a layer thickness of 2 / 5 of the p-type AlGaN layer, and a third region having a layer thickness of 1 / 2 of the p-type AlGaN layer, and the p-type AlGaN layer is defined as follows.
[0092] The Al composition curve in each region shows that the Al composition ratio is 1st region < 3rd region < 2nd region. The Mg concentration curve shows that the Mg concentration is less than 3×10 19 atoms / cm 3 , and the magnitude relationship between the Mg concentrations in the various regions is the first region < the second region < the third region. The Mg concentration in at least a portion of the second region is 3×10 18 atoms / cm 3 Above, the Mg concentration curve has a peak in the second region.
[0093] With the above structure, since an appropriate amount of Mg is contained in an appropriate region of the p-type AlGaN layer in the layer thickness direction, it is possible to suppress a decrease in device life due to excessive Mg while ensuring a sufficient hole carrier concentration in the p-type AlGaN layer.
[0094] Therefore, the surface emitting laser 10 of the present embodiment can suppress a decrease in the element life while ensuring high carrier injection efficiency, and can provide a vertical cavity light emitting element having a long life and high efficiency.
[0095] Reference Figure 5 and Figure 6 , an example of a method for manufacturing the surface emitting laser 10 is described. Figure 5 : is a flowchart showing an outline of a manufacturing process of the surface emitting laser 10. The formation of each semiconductor layer is performed using a metal organic chemical vapor deposition (MOCVD) method.
[0096] First, the base layer 13 is formed on the substrate 11, and then the first multilayer film reflecting mirror 15 is formed on the base layer 13 (step S11).
[0097] A C-plane GaN substrate is used as the substrate 11 as the growth substrate. Although not shown in the figure, in the semiconductor layer growth device, the substrate 11 is arranged on a susceptor. In addition, a thermocouple is arranged under the susceptor, and the temperature of the thermocouple is referred to as the "substrate temperature" in this specification. In addition, in this specification, the "growth temperature" refers to the substrate temperature.
[0098] In step S11, first, the temperature of the substrate 11 is raised to 1200° C., and trimethylgallium (hereinafter referred to as TMG) and ammonia (NH3) gas are supplied in a hydrogen carrier gas (atmosphere gas) to grow a 100 nm bottom layer 13 composed of undoped GaN. In the case of homoepitaxial growth, the bottom layer 13 does not necessarily need to be stacked, so the bottom layer is optional.
[0099] Subsequently, the first multilayer film reflecting mirror 15 is formed. On the base layer 13, a semiconductor distributed Bragg reflector (DBR) composed of a stacked body of InAlN / GaN is grown.
[0100] First, an InAlN layer is grown on the bottom layer 13. The substrate temperature is set to 950°C, and the carrier gas is nitrogen (N2) gas. Trimethylindium (hereinafter referred to as TMI) as an indium material gas, trimethylaluminum (hereinafter referred to as TMA) as an aluminum material gas, and ammonia gas are supplied to grow the InAlN layer.
[0101] Then, a GaN layer is grown on the InAlN layer. The substrate temperature is raised to 1100° C., the carrier gas is changed to hydrogen, and trimethylgallium (hereinafter referred to as TMG) and ammonia gas are supplied as gallium material gases to form a GaN layer on the InAlN layer.
[0102] Then, the above-mentioned process of growing the InAlN layer and the process of growing the GaN layer are further repeated 40 times, and a total of 41 pairs of InAlN layers and GaN layers are stacked. InAlN and GaN are formed in the layer on the (0001) plane of the crystal plane of the substrate 11, and the thickness of each layer is formed to 1 / 4 of the optical layer thickness of the desired wavelength.
[0103] Then, an n-type semiconductor layer 17 is formed on the first multilayer film reflecting mirror 15 (step S12). In step S12, TMG as a gallium material gas, ammonia as a nitrogen source gas, disilane (Si2H6) as an n-type doping material gas, and silicon-containing gas are supplied with a substrate temperature of 1200° C. and a carrier gas of hydrogen to form a 1500 nm thick layer doped with 3×10 18 atoms / cm 3 An n-type GaN layer (high temperature n-GaN layer) of Si.
[0104] After the n-type semiconductor layer 17 is formed, the active layer 19 is stacked on the n-type semiconductor layer 17 (step S13 ).
[0105] In step S13, a multi-quantum well layer (hereinafter referred to as MQW: Multi QuantumWell) is formed on the n-type semiconductor layer 17. The barrier layer and the well layer are made of In x Al y Ga 1-x-y In this embodiment, 3 nm of undoped InGaN (y=0) as a well layer and 4 nm of undoped GaN (x=y=0) as a barrier layer are stacked five times to form MQWs consisting of five pairs.
[0106] After forming active layer 19, p-type semiconductor layer 23 is formed on active layer 19 (step S14). In step S14, a GaN layer is formed as intermediate layer 21 with a thickness of 130 nm on active layer 19, and p-type semiconductor layer 23 is formed on intermediate layer 21.
[0107] Figure 6 A diagram schematically showing the growth sequence (p-type AlGaN layer growth step) of the p-type AlGaN layer 35 of the surface emitting laser 10. Figure 6 In the figure, the horizontal axis represents time T. In addition, Figure 6 The vertical axis in represents the substrate temperature Ts. Figure 6 In the figure, as the substrate temperature Ts changes over time, an ON state or an OFF state indicating whether supply is being performed is shown for each supply gas. In addition, among the types of supplied gases, for the material gas (TMA) of Al and the material gas (biscyclopentadienyl magnesium (hereinafter referred to as Cp2Mg) of Mg, the ON state is indicated as ON (high) when supplied in a large supply amount, and the ON state is indicated as ON (low) when supplied in a small supply amount.
[0108] like Figure 6 As shown, the p-type AlGaN layer 35 is grown in three steps. First, in the first growth step (step 1 in the figure), when the substrate temperature is increased from TP1 (950°C, first temperature) to TP2 (1000°C, second temperature) within a period of 30 seconds (time T = T1 to T2) with nitrogen and ammonia as carrier gases, 9.4 sccm (Standard Cubic Centimeters per Minute: standard cubic centimeters per minute) (first supply amount, turned on (high) in the figure) of TMA as Al material gas and 1.6 sccm of TMG as Ga material gas are supplied, and 37.2 sccm (second supply amount, turned on (high) in the figure) of Cp2Mg as Mg material gas are further supplied to grow the first p-type AlGaN layer ( Figure 3 Ammonia is used as the nitrogen source gas for the p-type AlGaN layer 35. The design value of the layer thickness of the first p-type AlGaN layer is 0.8 nm. The design value of the Al composition of the first p-type AlGaN layer is 25%.
[0109] In the second growth step (step 2 in the figure), the substrate temperature is maintained at TP2, and TMG, nitrogen, ammonia, TMA, and Cp2Mg are continuously supplied at the same level as in the first growth step, and a second p-type AlGaN layer ( Figure 3 In the second growth step, TMA is maintained to supply the first supply amount, and Cp2Mg is maintained to supply the second supply amount. The design value of the thickness of the second p-type AlGaN layer is 2.2 nm. The design value of the Al component of the second p-type AlGaN layer is 42%.
[0110] In the third growth step (step 3 in the figure), the substrate temperature is maintained at TP2, and while the supply amounts of TMG, nitrogen, and ammonia are maintained, TMA is supplied at 4.9 sccm (third supply amount, on (low) in the figure) which is less than the first supply amount, and Cp2Mg is supplied at 2.5 sccm (fourth supply amount, on (low) in the figure) which is less than the second supply amount, to grow (T=T3 to T4) the third p-type AlGaN layer ( Figure 3 The third layer 41 is shown in FIG. 4 ). The design value of the thickness of the third p-type AlGaN layer is 7 nm. In addition, the design value of the Al composition of the third p-type AlGaN layer is 28%.
[0111] Thus, a p-type AlGaN layer 35 having a design value of 10 nm was formed. The supply amount of the Mg material gas in the above-mentioned p-type AlGaN layer growth step does not correspond to the above-mentioned SIMS distribution. Specifically, as described above, the supply amount of the Mg material gas in the third growth step is greatly reduced to less than one-tenth of that in the first growth step and the second growth step. In contrast, Figure 4 In the SIMS analysis results shown, the Mg concentration curve shows that the Mg concentration is highest in the third region.
[0112] This is believed to be due to the fact that the higher the substrate temperature, the higher the decomposition efficiency of Cp2Mg, the easier it is for Mg to enter the growth layer, and also due to the memory effect of Mg. In the MOCVD method, it is known that there will be a phenomenon called memory effect in which the solid phase thermal diffusion of Mg dopant or the residual Mg raw material in the chamber is accidentally mixed into the film. For example, if the supply amount of Cp2Mg in the third growth step is too high, the Mg concentration in the p-type AlGaN layer 35 is excessive, for example, more than 3×10 19atoms / cm 3 , which will lead to a reduction in component life.
[0113] The above growth sequence takes these characteristics of Mg into consideration and adjusts the supply amount so that a desired SIMS distribution can be obtained. Specifically, by making the supply amount of Cp2Mg in the third growth step (the fourth supply amount) less than one tenth of the supply amount of Cp2Mg in the second growth step (the second supply amount), the Mg concentration is kept at no more than 3×10 19 atoms / cm 3 In this embodiment, nitrogen gas is used as a carrier gas instead of hydrogen gas which makes Mg easily bonded to the layer.
[0114] In this embodiment, by improving the above growth method, it is possible to form Figure 4 The SIMS profile of the p-type AlGaN layer 35 is shown. Therefore, this in turn suppresses an increase in the threshold current density of the surface emitting laser 10 and also suppresses a decrease in the lifetime.
[0115] After forming the p-type AlGaN layer 35, a 5×10 18 atoms / cm 3 A p-type GaN layer with Mg of 5×10 is used as the p-type nitride semiconductor layer 43. Then, a 5×10 20 atoms / cm 3 The above Mg p-type GaN contact layer serves as the p-type contact layer 45 , and the formation of the p-type semiconductor layer 23 is completed.
[0116] [Component production steps]
[0117] After forming the p-type semiconductor layer, Mg is activated by heat treatment in a rapid thermal annealing device (hereinafter referred to as "RTA"). Then, a mesa pattern is formed using a photoresist, and a mesa structure is formed by dry etching. At the same time, an exposed portion 17E that partially exposes the n-type semiconductor layer 17 is also formed around the mesa structure (see Figure 1 ). Then, the photoresist is removed.
[0118] Silicon oxide (SiO2) of 150 nm is formed on the mesa structure and the exposed portion 17E by sputtering as an insulating layer 27. Patterning is performed using a photoresist, etching is performed using buffered hydrofluoric acid (hereinafter referred to as "BHF"), and an opening OP is formed in the insulating layer 27 on the mesa structure as an opening for light emission. Then, the photoresist is removed.
[0119] Indium tin oxide (hereinafter referred to as "ITO") with a thickness of about 17 nm is formed by sputtering as a semi-transparent electrode 29. A pattern is formed using a photoresist, and the ITO is etched using a mixed acid to form a semi-transparent electrode 29 on the insulating layer 27 on the mesa structure and on the p-type contact layer 45 exposed through the opening OP of the insulating layer 27. Then, the photoresist is removed and heat treatment is performed using RTA to make the ITO transparent and improve its conductivity.
[0120] Electron beam (hereinafter referred to as "EB") deposition is used to form a p-side metal layer (p-electrode 33) with a thickness of about 300 nm that does not cover the opening on the semi-transparent electrode 29. A stack of platinum (Pt), gold (Au), and titanium (Ti) is used for the p-side metal layer. Next, the photoresist is removed by chemical stripping.
[0121] After patterning with a photoresist, an n-electrode 25 electrically connected to the exposed portion 17E of the n-type semiconductor layer 17 is formed by EB deposition to a thickness of about 700 nm. A stack of Ti, Al, Pt, and Au is used for the n-electrode. The photoresist is removed by chemical stripping.
[0122] Using EB deposition, 10.5 pairs (about 1300nm) of dielectric multilayer films (dielectric multilayer film reflectors, dielectric DBRs) as the second multilayer film reflectors 31 are formed on the semi-transparent electrode 29. The dielectric DBR uses a stack of niobium oxide (hereinafter referred to as Nb2O5, film thickness of about 45nm) and SiO2 (film thickness of about 76nm). Next, a dielectric DBR pattern is formed using a photoresist, and unnecessary portions of the dielectric DBR (on the p-electrode and on the n-electrode) are etched away using a dry etching device. Finally, the photoresist is removed using chemicals.
[0123] A pattern is formed using a photoresist, and an additional p-side metal layer (not shown) electrically connected to the p-electrode is formed with a thickness of about 2200 nm using EB deposition. A stack of Ti, Pt, and Au is used as the p-electrode (p-pad layer). Next, the photoresist is removed by stripping using chemicals. In this way, a device is manufactured (step S15).
[0124] The surface emitting laser 10 is manufactured using the above steps.
[0125] Reference Figure 7, describing the p-type AlGaN layer of the surface emitting laser of Comparative Example 1. The surface emitting laser of Comparative Example 1 differs from the surface emitting laser of Embodiment 1 in that, instead of the p-type AlGaN layer 35, a p-type AlGaN layer grown with a constant supply of 4.9 sccm of Al material gas (TMA) and a constant supply of 37.2 sccm of Mg material gas (Cp2Mg) is included, wherein the design value of the layer thickness is 10 nm and the design value of the Al component is 30%. In all other aspects, the surface emitting laser of Comparative Example 1 is configured in the same manner as Embodiment 1. In other words, the p-type AlGaN layer of Comparative Example 1 is grown in a single step and is grown using a method different from the growth method of Embodiment 1 which includes three steps.
[0126] Figure 7 The SIMS analysis results of the p-type AlGaN layer of the surface emitting laser of Comparative Example 1 are shown. Figure 4 The same graph is shown, Figure 7 In FIG. 1 , the Al composition curve showing the change of the Al composition in the depth direction is indicated by a dotted line, and the Mg concentration curve showing the change of the Mg concentration in the depth direction is indicated by a solid line. Figure 4 Similarly to the case of embodiment 1 shown, the width at 50% of the maximum peak of the Al component is defined as the p-type AlGaN layer, and the p-type AlGaN layer is divided into a first region AR1 with a layer thickness of 10%, a second region AR2 with a layer thickness of 40%, and a third region AR3 with a layer thickness of 50% from the active layer side toward the surface side of the p-type AlGaN layer 35.
[0127] like Figure 7 As shown, the Mg concentration curve has a peak in the second region AR2 and exceeds 3×10 19 atoms / cm 3 Therefore, when the Mg concentration in the second region becomes more than 3×10 19 atoms / cm 3 When the concentration of Mg is high, the injection efficiency of carriers becomes high, but the diffusion of Mg into the active layer and the extension of defects caused by Mg into the active layer are more likely to occur, and this reduces the element life.
[0128] Reference Figure 8 , describing the p-type AlGaN layer of the surface emitting laser of Comparative Example 2. The surface emitting laser of Comparative Example 2 is different from the surface emitting laser of Embodiment 1 or Comparative Example 1 in that it includes a p-type AlGaN layer grown using a method different from that of the p-type AlGaN layer 35 of Embodiment 1 and the p-type AlGaN layer of Comparative Example 1, and is configured similarly to Embodiment 1 in other respects.
[0129] The p-type AlGaN layer of Comparative Example 2 has a Mg concentration of less than 3×10 19 atoms / cm 3 In Comparative Example 2, the maximum Mg concentration was 0.9×10 19 atoms / cm 3 , 2.0×10 19 atoms / cm 3 , 2.6×10 19 atoms / cm 3 Three samples of .
[0130] The maximum Mg concentration is 0.9×10 19 atoms / cm 3 The sample (hereinafter also referred to as "Sample 1") was grown by maintaining the supply amount of Al material gas (TMA) at 6.0 sccm and the supply amount of Mg material gas (Cp2Mg) at 37.2 sccm, where the design value of the layer thickness is 10 nm and the design value of the Al component is 30%.
[0131] The maximum Mg concentration is 2.0×10 19 atoms / cm 3 The sample (hereinafter also referred to as "Sample 2") was grown by maintaining the supply amount of Al material gas (TMA) at 6.0 sccm and supplying 37.2 sccm of Mg material gas (Cp2Mg) until 5nm, and then supplying 2.5 sccm to grow another 5nm, and the sample was grown with a design value of layer thickness of 10nm and a design value of Al component of 30%.
[0132] The maximum Mg concentration is 2.6×10 19 atoms / cm 3 The sample (hereinafter also referred to as "Sample 3") was grown by maintaining the supply amount of Al material gas (TMA) at 4.9sccm and supplying 37.2sccm of Mg material gas (Cp2Mg) until 5nm, and then supplying 2.5sccm to grow another 5nm, and the sample was grown with a designed value of layer thickness of 10nm and a designed value of Al component of 30%.
[0133] Figure 8 The SIMS analysis results of the p-type AlGaN layer of the surface emitting laser of Comparative Example 2 are shown. Figure 8 In the figure, the Al composition curve showing the change of the Al composition in the depth direction is indicated by the dotted line, and the Mg concentration curve showing the change of the Mg concentration in the depth direction is indicated by the solid line. 19 atoms / cm3 The Al composition curve and Mg concentration curve of the sample (sample 2) are represented by thicker lines than those of sample 1. 19 atoms / cm 3 For the sample (sample 3), the Al composition curve and the Mg concentration curve are represented by thicker lines than those of sample 2.
[0134] exist Figure 8 In the Mg concentration curve of sample 3, the maximum Mg concentration is less than 3×10 19 atoms / cm 3 , the Mg concentration in the first region AR1 is low, and has a peak in the third region AR3 farthest from the active layer. Therefore, since the peak concentration of Mg is low and the peak exists in a region far from the active layer, it is preferable in that diffusion of Mg into the active layer and influence of defects caused by Mg on the active layer are unlikely to occur.
[0135] On the other hand, the Mg concentration curve of sample 3 decreases monotonically toward the active layer in the second region AR2. In this case, it can be seen that although the hole carrier concentration exceeds 3×10 18 atoms / cm 3 The fact that is one of the indicators for obtaining a sufficient hole carrier concentration in almost the entire second region AR2, but the hole carrier concentration is insufficient and the overflow of electron carriers cannot be suppressed, the carrier injection efficiency decreases, and the threshold current density increases.
[0136] Sample 2 also has a value less than 3×10 19 atoms / cm 3 The concentration of sample 1 is less than 1×10 19 atoms / cm 3 Therefore, it is preferable in that diffusion of Mg into the active layer and influence of defects caused by Mg on the active layer are unlikely to occur.
[0137] However, in Sample 2 and Sample 1, the Mg concentration in the second region AR2 is further reduced compared to the case of Sample 3, the hole carrier concentration is insufficient, and the carrier injection efficiency is reduced.
[0138] As reference Figure 7 and Figure 8 As described above, in Comparative Example 1, a Mg peak concentration of 3×10 19 atoms / cm 3 The above samples were prepared in Comparative Example 2 with a peak concentration of Mg less than 3×10 19 atoms / cm 3 samples, but in both cases the Mg concentration distribution cannot be properly controlled.
[0139] Specifically, in Comparative Example 1, if the peak concentration of Mg is set to 3×10 19 atoms / cm 3 As a result, a peak with high Mg concentration appears in a region close to the active layer 19, and the diffusion of Mg into the active layer and the influence of defects caused by Mg on the active layer become greater, which reduces the life of the device.
[0140] In Comparative Example 2, if the peak concentration of Mg is set to 3×10 19 atoms / cm 3 Below, the peak position of the Mg concentration curve becomes the third region AR3, and the Mg concentration in the second region decreases monotonically toward the active layer, and the reduction of hole carriers leads to a decrease in carrier injection efficiency, thereby causing an increase in the threshold current density. The increase in the threshold current density will also reduce the life of the element.
[0141] In contrast, in the first embodiment, the Mg concentration indicated by the Mg concentration curve is less than 1×10 19 atoms / cm 3 , and the Mg concentration profile has a value of more than 3×10 19 atoms / cm 3 The p-type AlGaN layer 35 showing such a Mg distribution can provide a sufficient hole carrier concentration in the p-type AlGaN layer while suppressing the reduction of the device life caused by excessive Mg. The p-type AlGaN layer 35 showing such a Mg distribution can be used by using a layer including Figure 6 The three-step method shown is used to achieve growth.
[0142] In this embodiment, the thickness of the first p-type AlGaN layer is preferably 0.4 nm to 1 nm. If it is less than 0.4 nm, the effect of suppressing the diffusion of Mg into the active layer and the extension of defects caused by Mg into the active layer is poor, and if it exceeds 1 nm, there is a risk of increasing the device voltage.
[0143] In the present embodiment, the design value of the Al composition of the first p-type AlGaN layer is preferably 25% or less. This is because if the Al composition exceeds 25%, there is a risk that the device voltage may increase.
[0144] In this embodiment, the design value of the Al component of the second p-type AlGaN layer is preferably 33% or more and 50% or less. If the Al component is less than 33%, it is easier to generate overflow of electron carriers and the threshold current density is more likely to increase. If the Al component exceeds 50%, the effects of the decrease in crystallinity of the p-type AlGaN layer, the generation of cracks, the increase in operating voltage, etc. become greater.
[0145] In this embodiment, the thickness of the second p-type AlGaN layer is preferably 2 nm or more and 6 nm or less. If the thickness is less than 2 nm, it is difficult to make the Mg concentration of the second region 3×10 18 atoms / cm 3 If the thickness exceeds 6 nm, the device voltage may increase significantly.
[0146] In this embodiment, the design value of the Al component of the third p-type AlGaN layer is preferably greater than 20% and less than 30%. By setting the Al component of the third p-type AlGaN layer within this range, the occurrence of cracks and the increase in operating voltage can be suppressed, and the overflow of electron carriers can be suppressed together with the second p-type AlGaN layer.
[0147] In addition, in the present embodiment, the thickness of the third p-type AlGaN layer is preferably greater than the thickness of the second p-type AlGaN layer. By making the thickness of the third p-type AlGaN layer thicker than the thickness of the second p-type AlGaN layer, the average Al composition of the entire p-type AlGaN layer 35 can be reduced, while suppressing the generation of cracks.
[0148] Implementation Method 2
[0149] Reference Fig. 9 , the structure of the surface emitting laser 50 according to Embodiment 2 is described. The surface emitting laser 50 is similar to the surface emitting laser 50 of reference Figures 1 to 3 The surface emitting laser 10 of the first embodiment described is similarly configured. However, only the structure of the p-type AlGaN layer 35 is different from that of the p-type AlGaN layer of the surface emitting laser 10. Specifically, the distribution of the Al composition and the Mg concentration in the layer thickness direction obtained by SIMS analysis of the p-type AlGaN layer 35 of the second embodiment is different from that of the first embodiment.
[0150] Fig. 9 The results of SIMS analysis of the p-type AlGaN layer 35 of the surface emitting laser 50 performed in the same manner as in Embodiment 1 are shown. Fig. 9 In the same manner as in Embodiment 1, the entire width at half the maximum value of the Al composition (%) is defined as the p-type AlGaN layer 35, and the p-type AlGaN layer 35 is sequentially divided into first to third regions AR1 to AR3 in the layer thickness direction. Fig. 9In FIG. 1 , the Al composition curve is represented by a dotted line, and the Mg concentration curve is represented by a solid line.
[0151] like Fig. 9 As shown in the Mg concentration curve, the Mg concentration in the entire layer thickness of the p-type AlGaN layer 35 is less than 1×10 19 atoms / cm 3 , which is the same as in Embodiment 1. In addition, when the average values of the Mg concentrations in each region shown by the Mg concentration curve are compared between the regions, the third region AR3 is the largest, the second region AR2 is the second largest, and the first region AR1 is the smallest (the first region AR1<the second region AR2<the third region AR3), which is also the same as in Embodiment 1. By controlling the Mg concentration in the entire layer thickness of the p-type AlGaN layer 35 and the Mg concentration in each region, the diffusion of Mg into the active layer and the extension of defects caused by Mg into the active layer are suppressed, thereby suppressing the reduction of the element life.
[0152] exist Fig. 9 In the Mg concentration curve shown, the average Mg concentration in the second region is 3×10 19 atoms / cm 3 Above. Fig. 9 As shown, the Mg concentration curve has a peak in the third region and includes a portion (substantially flat portion) that extends to a portion of the second region AR2 and a portion of the third region AR3 centered at the boundary between the second region AR2 and the third region AR3 and is flatter than other portions.
[0153] In more detail, Fig. 9 In the graph, when the Mg concentration curve in the second region is divided into a portion on the first region side and a portion on the third region side with the center of the second region in the layer thickness direction as a dividing line, the slope of the portion on the third region side is gentler than the slope of the portion on the first region side.
[0154] exist Fig. 9 In the example graph shown in FIG. 1 , the absolute value of the slope of the approximate formula for the first region side (hereinafter, the slope is expressed by the absolute value) is approximately 2×10 18 , and the slope of the approximate formula of the third region side is about 2×10 17 In other words, it can be said that the average value of the slope of the Mg concentration curve in the second region in the portion on the third region side relative to the center of the second region in the layer thickness direction is smaller than the average value of the slope in the portion on the first region side.
[0155] It can be seen that even when the Mg concentration is controlled to the above distribution, it is possible to prevent the Mg concentration in the second region from becoming too low and ensure sufficient carrier injection efficiency. In the surface emitting laser 50 of the second embodiment, the average value of the Mg concentration in the second region is 3×10 18 atoms / cm 3 In the Mg concentration curve in the second region, the average value of the slope at the third region side relative to the center of the second region in the layer thickness direction is controlled to be smaller than the average value of the slope at the first region side, thereby ensuring sufficient carrier injection efficiency, thereby suppressing the increase in threshold current density.
[0156] In this embodiment, when the average value of the Al composition in each region shown by the Al composition curve is compared between the regions, the second region AR2 is the largest, the third region AR3 is the second largest, and the first region AR1 is the smallest (first region AR1<third region AR3<second region AR2), which is the same as embodiment 1.
[0157] [Manufacturing method of embodiment 2]
[0158] The p-type AlGaN layer 35 of the second embodiment is Figure 6 In Embodiment 2, the p-type AlGaN layer 35 is grown under conditions where the supply amount of TMA as the Al material gas, the design value of the layer thickness, and the design value of the Al composition in Steps 1 and 2 are different from those in Embodiment 1, and the other conditions are the same as those in Embodiment 2.
[0159] Specifically, Embodiment 2 differs from Embodiment 1 in that the first supply amount of TMA is set to 6.2 sccm, the designed layer thickness of the first p-type AlGaN layer is set to 0.6 nm, the designed value of the Al component is set to 23%, the designed layer thickness of the second p-type AlGaN layer is set to 2.4 nm, and the designed value of the Al component is set to 33% lower than the designed value of Embodiment 1. The supply amounts of nitrogen gas and ammonia gas as the atmosphere gas and the supply amount of TMG as the gallium material gas are the same as those of Embodiment 1.
[0160] Therefore, by adjusting the Al composition ratio according to the supply amount of TMA, it is possible to adjust how Mg is incorporated into the film. When SIMS analysis was performed on the grown p-type AlGaN layer 35, it was found that Fig. 9 Specifically, a Mg concentration curve is obtained in which the average Mg concentration in the second region is 3×10 18 atoms / cm 3As above, the average value of the slope at the portion on the third region side with respect to the center of the second region in the layer thickness direction is smaller than the average value of the slope at the portion on the first region side.
[0161] Therefore, the manufacturing method of the surface emitting laser 50 including the growth method of the p-type AlGaN layer 35 of embodiment 2 enables the formation of a p-type AlGaN layer containing an appropriate amount of Mg in an appropriate region in the layer thickness direction of the p-type AlGaN layer, and is able to suppress the reduction in element life caused by excess Mg while ensuring a sufficient hole carrier concentration.
[0162] Therefore, the surface emitting laser 50 of the present embodiment can suppress reduction in the life of the element while ensuring high carrier injection efficiency, and can provide a vertical cavity light emitting element with long life and high efficiency.
[0163] [Modifications]
[0164] Reference Figures 10 to 14 , the structure of a surface emitting laser 60 according to a modification of Embodiment 2 is described. The surface emitting laser 60 is configured similarly to the surface emitting laser 50 of Embodiment 2, and only a part of the growth method of the p-type AlGaN layer 35 is different.
[0165] Fig.10 The Al composition curve (Al-A) and the Mg concentration curve (Mg-A) obtained by SIMS analysis of the sample A of the p-type AlGaN layer 35 of the surface emitting laser 60 are shown. Similar to the case of Embodiment 2, the entire width range at half the maximum value of the Al composition curve (Al-A) is defined as the p-type AlGaN layer 35, and the p-type AlGaN layer 35 is divided into the first region AR1 to the third region AR3 in the layer thickness direction. Fig.10 In the figure, the Al composition curve of Embodiment 2 is represented as Al-EX2, and the Mg concentration curve is represented as Mg-EX2.
[0166] like Fig.10 As shown, the Mg concentration profile of the p-type AlGaN layer 35 of the surface emitting laser 60 has the same characteristics as the Mg concentration profile according to Embodiment 2. Specifically, the Mg concentration profile Mg-A according to the modified example has the same characteristics as Mg-EX2 of Embodiment 2 in that the average value of the slope at the portion on the third region side relative to the center of the second region in the layer thickness direction is smaller than the average value of the slope at the portion on the first region side.
[0167] However, if Fig.10As shown, the Mg concentration curve of the p-type AlGaN layer 35 of the surface emitting laser 60 is shifted toward the high concentration side compared with the Mg concentration curve of Embodiment 2. The shift toward the high concentration side is significant in the region from the second region to the third region, particularly in the region including the substantially flat portion forming the peak shoulder of the third region centered on the boundary between the second region and the third region. The increase in the Mg concentration in this flat portion is preferable in terms of increasing the hole carrier concentration and improving the carrier injection efficiency.
[0168] The above-mentioned shift of the Mg concentration distribution toward the high concentration side is caused by adding a step of supplying the Mg material gas before starting the growth of the p-type AlGaN layer 35. A method of manufacturing the p-type AlGaN layer 35 of the surface emitting laser 60 is described below.
[0169] Fig.11 Schematically showing the p-type AlGaN layer growth step, this figure is a diagram showing the growth sequence of the sample A of the p-type AlGaN layer 35 of the surface emitting laser 60. Fig.11 As shown, in this modification, after the temperature raising step as a pre-treatment step, the p-type AlGaN layer is grown in three steps.
[0170] In the temperature raising step, the substrate temperature is raised from TP1 (950°C, first temperature) to TP2 (1000°C, second temperature) within 30 seconds (time T = T1 to T2), the carrier gas is nitrogen and ammonia, and the Mg material gas (Cp2Mg) is supplied at 37.2 sccm (first supply amount, on (high) in the figure). In the temperature raising step, the Al material gas (TMA) and the Ga material gas (TMG) are not supplied. Therefore, in the temperature raising step, the p-type AlGaN layer is not grown.
[0171] After the temperature raising step, in the first growth step (step 1 in the figure), the substrate temperature is maintained at TP2 (1000°C, the second substrate temperature), and the carrier gas is continuously supplied with nitrogen and ammonia as nitrogen source gases. In the first growth step, TMA as the Al material gas is supplied at 6.2 sccm (the second supply amount, turned on (high) in the figure), and TMG as the Ga material gas is supplied at 1.6 sccm (turned on in the figure). In addition, the Mg material gas (Cp2Mg) is supplied at 37.2 sccm (the third supply amount, turned on (high) in the figure). Under these conditions, the first p-type AlGaN layer ( Figure 3 The first layer 37 is shown in FIG. 1 ). The designed value of the thickness of the first p-type AlGaN layer is 0.6 nm. The designed value of the Al composition of the first p-type AlGaN layer is 25%.
[0172] After the first growth step, the second growth step (step 2 in the figure) and the third growth step (step 3 in the figure) are performed in the same manner as the second growth step and the third growth step in Embodiment 2.
[0173] In the second growth step, the substrate temperature is maintained at TP2, TMG, nitrogen and ammonia, TMA and Cp2Mg are supplied in such a manner as to maintain the supply amounts in the first growth step, and a second p-type AlGaN layer ( Figure 3 In the second growth step, TMA is supplied at a maintained second supply amount, and Cp2Mg is supplied at a maintained third supply amount. The design value of the thickness of the second p-type AlGaN layer is 2.4 nm. The design value of the Al component of the second p-type AlGaN layer is 33%.
[0174] After the second growth step, in the third growth step, the substrate temperature is maintained at TP2, and the supply amounts of TMG, nitrogen, and ammonia are maintained at the same time, and TMA is supplied at 4.9 sccm (a fourth supply amount, which is turned on (low) in the figure) which is lower than the second supply amount, and Cp2Mg is supplied at 2.5 sccm (a fifth supply amount, which is turned on (low) in the figure) which is lower than the third supply amount, to grow (T=T4 to T5) the third p-type AlGaN layer ( Figure 3 The third layer 41 is shown in FIG. 1 . The design value of the thickness of the third p-type AlGaN layer is 7 nm. The design value of the Al composition of the third p-type AlGaN layer is 28%.
[0175] As described above, the p-type AlGaN layer 35 according to the modification example is formed at the designed value of 10 nm.
[0176] In the above description, an example is described in which the processing time (T1 to T2) in the temperature rising step (i.e., the temperature rising time) is set to 30 seconds and the supply amount (first supply amount) of the Mg material gas is set to 37.2 sccm. In this modification, it can be seen that by adjusting the temperature rising time and the supply amount of the Mg material gas, the Mg concentration in the second region can be adjusted.
[0177] Fig.12 Shown in Fig.11 The Al composition curve and Mg concentration curve of sample B of the p-type AlGaN layer 35 grown under the same conditions as described in , except that the Mg material gas supply amount (first supply amount) during the temperature increase step is set to 75 sccm and the temperature increase time is set to 15 seconds, and the results of embodiment 2.
[0178] In the region including the substantially flat portion of the shoulder of the peak of the third region centered at the boundary between the second region and the third region, the Mg concentration curve is shifted toward the high concentration side compared to Embodiment 2. The increase in Mg concentration of Sample B is 2.3 times greater than that of Embodiment 2. Fig.10 The rise in sample A shown in is approximately the same.
[0179] Fig.13 Shown in Fig.11 The Al composition curve and Mg concentration curve of the sample C of the p-type AlGaN layer 35 grown under the same conditions as described above (except that the Mg material gas supply amount (first supply amount) during the temperature increase step is set to 37.5 sccm and the temperature increase time is set to 15 seconds). The increase in Mg concentration is greater than Fig.10 The sample A shown has a small rise. However, the sample C has a thickness of less than 1×10 19 atoms / cm 3 According to the conditions of sample C, it can be said that the Mg concentration in the second region can be less than 1×10 19 atoms / cm 3 The concentration of the ions is shifted toward the high concentration side within the range of .
[0180] From the above, it can be seen that the Mg concentration in the flat portion of the Mg concentration distribution in the second region (i.e., the portion on the third region side relative to the center of the second region in the layer thickness direction) increases according to the temperature increase time in the temperature increase step (i.e., the supply time of the Mg material gas and the supply amount of the Mg material gas). In addition, it can be seen that the increase in the Mg concentration in the flat portion is generally related to the product of the supply time and the supply amount of the Mg material gas.
[0181] As described above, the Mg memory effect is easily generated when growing a p-type AlGaN layer, and the higher the substrate temperature, the easier it is for Cp2Mg to decompose into Mg. In this variant, considering the memory effect and the influence of the substrate temperature, in the temperature increase step, by first supplying the Mg material gas, the Mg concentration distribution can be reliably controlled.
[0182] As described above, according to the p-type AlGaN layer growth step of this modification, the Mg concentration in the p-type AlGaN layer is less than 3×10 19 atoms / cm 3 , preferably less than 1×10 19 atoms / cm 3 , and the average Mg concentration in the second region is 3×10 18 atoms / cm 3The Mg concentration profile in the second region can be reliably controlled so that the average value of the slope at the third region side relative to the center of the second region in the layer thickness direction is smaller than the average value of the slope at the first region side.
[0183] Implementation 3
[0184] Reference Figures 14 to 16 , the surface emitting laser 70 of Embodiment 3 is described. Fig.14 2 is a cross-sectional view showing the structure of a surface emitting laser 70. The surface emitting laser 70 is basically configured in the same manner as the surface emitting laser 10 of the first embodiment and the surface emitting laser 50 of the second embodiment.
[0185] The surface emitting laser 70 is different from the surface emitting laser 10 or the surface emitting laser 50 in that it includes a p-type AlGaN layer 71 of a five-layer structure instead of the p-type AlGaN layer 35 of a three-layer structure.
[0186] The p-type AlGaN layer 71 is formed on the intermediate layer 21 similarly to the p-type AlGaN layer 35 , and is an AlGaN layer doped with Mg as a p-type impurity to function as an electron blocking layer.
[0187] The p-type AlGaN layer 71 is composed of five p-type AlGaN layers with different Mg concentration distributions and Al composition distributions. Fig.14 , five layers constituting the p-type AlGaN layer 71 are shown as a first layer 72 , a second layer 73 , a third layer 74 , a fourth layer 75 , and a fifth layer 76 .
[0188] Fig.15 FIG. 2 shows the results of SIMS analysis of the p-type AlGaN layer 71 of the surface emitting laser 70 performed in the same manner as in Embodiment 2. Fig.15 In the embodiment 2, the entire width range at half the maximum value of the Al composition (%) is defined as the p-type AlGaN layer 71, and the p-type AlGaN layer 71 is divided into the first region AR1 to the third region AR3 in the layer thickness direction. Fig.15 In FIG. 1 , the Al composition curve is represented by a dotted line, and the Mg concentration curve is represented by a solid line.
[0189] like Fig.15 As shown, the Al composition profile and the Mg concentration profile of the p-type AlGaN layer 71 have the same characteristics as those of the second embodiment.
[0190] Specifically, the Mg concentration shown in the Mg concentration curve of the p-type AlGaN layer 71 is less than 1×10 19 atoms / cm 3 , which is consistent with Fig. 9 The analysis results of the embodiment 2 shown are the same. In addition, when the average values of the Mg concentration in each region shown by the Mg concentration curve are compared between the regions, the third region AR3 is the largest, the second region AR2 is the second largest, and the first region AR1 is the smallest (the first region AR1<the second region AR2<the third region AR3), which is the same as the embodiment 1.
[0191] The average Mg concentration in the second region of the p-type AlGaN layer 71 is also 3×10 18 atoms / cm 3 The above is the same as the analysis result of Implementation 2.
[0192] Furthermore, in the Mg concentration curve of the p-type AlGaN layer 71, when the second region is at the center in the layer thickness direction, the region close to the first region is taken as the lower layer and the region close to the third region is taken as the upper layer, the slope becomes smaller in the upper layer compared to the second embodiment. In other words, the shoulder of the peak in the third region becomes flatter. In addition, the Mg concentration in the upper layer is 5×10 18 atoms / cm 3 above.
[0193] As described above, in the Mg concentration curve of the p-type AlGaN layer, if a flat portion appears in the region close to the third region from the center of the second region in the layer thickness direction, the hole carrier concentration can be sufficiently obtained, the carrier injection efficiency becomes high, and the threshold current density can be suppressed to a low level. Therefore, in this embodiment, a high hole carrier concentration can also be obtained in the p-type AlGaN layer 71. Therefore, it can be said that the surface emitting laser 70 has a high carrier injection efficiency and a low threshold current density, and the device life is long.
[0194] Fig.16 is a diagram schematically showing a growth sequence (p-type AlGaN layer growth step) of the p-type AlGaN layer 71 of the surface emitting laser 70 .
[0195] like Fig.16 As shown, the p-type AlGaN layer 71 is grown in five steps. Fig.16 The growth sequence shown before step 3 is similar to Figure 6 The growth sequence is performed in the same manner as in the embodiment 1 shown in the figure, but in this embodiment, the designed film thickness of step 3 is smaller than that of embodiment 1. The difference between this embodiment and embodiment 1 is that after step 3, in steps 4 and 5, the steps corresponding to step 2 and step 3 of embodiment 1 are repeated with a smaller designed layer thickness. Table 1 shows an example of growth conditions including the supply amount of each material gas when growing the p-type AlGaN layer 71 and the designed layer thickness.
[0196] [Table 1]
[0197]
[0198] like Fig.16 As shown in Table 1, in steps 1 to 5, the carrier gas is ammonia (NH 3 ) gas and nitrogen gas as nitrogen source gas, and TMG as Ga material gas is supplied at a certain supply amount of 1.6 sccm.
[0199] The first growth step (step 1 in the figure) is performed in the same manner as in Embodiment 1. In the first growth step, while supplying TMA as the Al material gas at 9.4 sccm (first supply amount, on (high) in the figure) and supplying the Mg material gas (Cp2Mg) at 37.2 sccm (second supply amount, on (high) in the figure), the substrate temperature is raised from TP1 (950° C., first temperature) to TP2 (1000° C., second temperature) within 30 seconds (time T=T1 to T2), thereby growing the first p-type AlGaN layer ( Fig.14 The first layer 72 is shown in the figure.
[0200] In the second growth step (step 2 in the figure), the substrate temperature is maintained at TP2 (1000°C), the supply amount of TMA and the supply amount of Cp2Mg are not changed, and the second p-type AlGaN layer ( Fig.14 The second layer 73 is in the middle).
[0201] In the third growth step (step 3 in the figure), the supply amount of TMA is set to 4.9 sccm (third supply amount, on (low) in the figure), and the supply amount of Cp2Mg is set to less than one tenth of the second supply amount, that is, 2.5 sccm (fourth supply amount, on (low) in the figure), and the third p-type AlGaN layer ( Fig.14 The third layer 74 is in the middle).
[0202] In the fourth growth step (step 4 in the figure), the supply amount of TMA is set to 9.4 sccm again (the first supply amount, which is turned on (high) in the figure), and the supply amount of Cp2Mg is maintained at 2.5 sccm (the fourth supply amount, which is turned on (low) in the figure), and the fourth p-type AlGaN layer ( Fig.14 The fourth layer 75 is in the middle).
[0203] In the fifth growth step (step 5 in the figure), the supply amount of TMA is reduced to 4.9 sccm (the third supply amount, which is turned on (low) in the figure), and the supply amount of Cp2Mg is maintained at 2.5 sccm (the fourth supply amount, which is turned on (low) in the figure), and the fifth p-type AlGaN layer ( Fig.14 The fifth layer 76 is shown in the figure.
[0204] In this way, a p-type AlGaN layer 71 with a designed value of 10 nm is formed. After step 3, more Mg enters the layer due to the memory effect of Mg. As described above, by reducing the supply amount of CP2Mg from step 3 to step 2 to less than one tenth of the first supply amount, the Mg concentration can be maintained at less than 3×10 19 atoms / cm 3 .
[0205] In Embodiment 3, the thickness of the first p-type AlGaN layer is preferably 0.4 nm to 1 nm. If it is less than 0.4 nm, the effect of suppressing the diffusion of Mg into the active layer and the extension of defects caused by Mg into the active layer is poor, and if it exceeds 1 nm, there is a risk of causing an increase in the device voltage.
[0206] In the present embodiment, the design value of the Al composition of the first p-type AlGaN layer is preferably 25% or less. This is because if the Al composition exceeds 25%, there is a risk of an increase in the device voltage.
[0207] In this embodiment, the design value of the Al component of the second p-type AlGaN layer and the fourth p-type AlGaN layer is preferably 33% or more and 50% or less. If the Al component is less than 33%, it is easier to generate overflow of electron carriers and the threshold current density is more likely to increase. If the Al component exceeds 50%, the effects of the decrease in crystallinity of the p-type AlGaN layer, the generation of cracks, the increase in operating voltage, etc. become greater.
[0208] In this embodiment, the thickness of the second p-type AlGaN layer is preferably 2 nm or more and 3 nm or less. If the thickness is less than 2 nm, it is difficult to make the Mg concentration of the second region 3×10 18 atoms / cm 3 If the thickness exceeds 3 nm, there is a risk of an increase in device voltage due to interaction with the fourth p-type AlGaN layer. Similarly, the thickness of the fourth p-type AlGaN layer is preferably not less than 2 nm and not more than 3 nm.
[0209] In this embodiment, the design value of the Al component of the third p-type AlGaN layer and the fifth p-type AlGaN layer is preferably greater than 20% and less than 30%. By setting the Al component of the third p-type AlGaN layer and the fifth p-type AlGaN layer within this range, the generation of cracks and the increase in the operating voltage can be suppressed, and the overflow of electron carriers can be suppressed by combining with the second p-type AlGaN layer and the fourth p-type AlGaN layer.
[0210] As described above, according to the p-type AlGaN layer growth step of the present embodiment, the p-type AlGaN layer is grown in the five steps described above so that the Mg concentration in the p-type AlGaN layer is less than 3×10 19 atoms / cm 3 , preferably less than 1×10 19 atoms / cm 3 , and the average Mg concentration in the second region is 3×10 18 atoms / cm 3 The Mg concentration profile in the second region can be reliably controlled so that the average value of the slope at the third region side relative to the center of the second region in the layer thickness direction is smaller than the average value of the slope at the first region side.
[0211] In the above embodiment, an example in which the thickness of the p-type AlGaN layer is 10 nm is described, but the invention is not limited thereto. The thickness of the p-type AlGaN layer is preferably 8 nm or more and 15 nm or less. If the thickness is less than 8 nm, electron carriers are easily overflowed and the threshold current density is easily increased. If the thickness exceeds 15 nm, there is a risk of cracks and an increase in the operating voltage.
[0212] In the above-mentioned embodiment, the difference between the Al composition in the second region and the Al composition in the third region shown by the Al composition curve is preferably 3% or more and 18% or less. For example, if the difference between the maximum Al composition in the second region and the maximum Al composition in the third region (hereinafter, referred to as "the difference in Al composition") is 3% or more, a flat portion appears in the second region of the Mg concentration curve as in Embodiments 2 and 3, and when the difference in Al composition exceeds 8%, a peak appears in the second region of the Mg concentration curve as in Embodiment 1. However, if the difference in Al composition is 18% or more, the crystallinity of the p-type AlGaN layer begins to deteriorate, which is not preferable.
[0213] In the above embodiment, a nitride semiconductor multilayer film is used as a reflector at the bottom. Since the thermal conductivity of the nitride semiconductor multilayer film containing AlInN is low, the resonator length is long. Therefore, in a surface emitting laser using a nitride semiconductor multilayer film as a reflector, the threshold current density is particularly likely to increase, thereby tending to cause carrier overflow. Therefore, it is effective to apply the present invention to a vertical cavity light-emitting element using a nitride semiconductor containing AlInN as a reflector.
[0214] The configurations in the above-described embodiments and manufacturing methods are merely examples and can be appropriately changed according to the intended use and the like.
[0215] Explanation of symbols
[0216] 10, 50, 60, 70: surface emitting laser
[0217] 11: Substrate
[0218] 15: The first multilayer reflector
[0219] 17: n-type semiconductor layer
[0220] 19: Active layer
[0221] 21: Middle layer
[0222] 23: p-type semiconductor layer
[0223] 25: n electrode
[0224] 27: Insulation layer
[0225] 29: Semi-transparent electrode
[0226] 31: Second multilayer reflector
[0227] 33: p electrode
Claims
1. A vertical cavity light emitting element, comprising: substrate; A first multilayer film reflector as a semiconductor multilayer film, in which two semiconductor layers having mutually different refractive indices are alternately stacked multiple times on the substrate; an n-type nitride semiconductor layer formed on the first multilayer film reflecting mirror and made of a nitride semiconductor containing an n-type dopant; an active layer, the active layer being formed on the n-type nitride semiconductor layer; a p-type AlGaN layer formed on the active layer and containing Mg as a p-type dopant, the p-type AlGaN layer having a structure in which three or more AlGaN layers having different Al compositions are stacked; a p-type nitride semiconductor layer formed on the p-type AlGaN layer, the p-type nitride semiconductor layer being a semiconductor layer made of a nitride semiconductor containing a p-type dopant; as well as a second multilayer film reflecting mirror, the second multilayer film reflecting mirror being formed on the p-type nitride semiconductor layer and being disposed at a position opposite to the first multilayer film reflecting mirror; wherein, in an Al composition curve indicating a change in the Al composition in the p-type AlGaN layer in a layer thickness direction and a Mg concentration curve indicating a change in the Mg concentration in the p-type AlGaN layer in a layer thickness direction, which are obtained by secondary ion mass spectrometry (SIMS) analysis of the p-type AlGaN layer, When the width range at 50% of the peak of the Al composition curve is defined as the p-type AlGaN layer, and the p-type AlGaN layer is divided into a first region having a layer thickness of 1 / 10 of the p-type AlGaN layer, a second region having a layer thickness of 2 / 5 of the p-type AlGaN layer, and a third region having a layer thickness of 1 / 2 of the p-type AlGaN layer in order from the active layer side in the layer thickness direction, The magnitude relationship between the Al components in each region indicated by the Al composition curve is: the first region < the third region < the second region. The Mg concentration indicated by the Mg concentration curve is less than 3×10 19 atoms / cm 3 , and the relationship between the Mg concentrations in each region is: the first region < the second region < the third region, The Mg concentration in at least a portion of the second region is 3×10 18 atoms / cm 3 Above, and The Mg concentration curve has a peak in the second region.
2. A vertical cavity light emitting element, comprising: substrate; A first multilayer film reflector as a semiconductor multilayer film, in which two semiconductor layers having mutually different refractive indices are alternately stacked multiple times on the substrate; an n-type nitride semiconductor layer formed on the first multilayer film reflecting mirror and made of a nitride semiconductor containing an n-type dopant; an active layer, the active layer being formed on the n-type nitride semiconductor layer; a p-type AlGaN layer formed on the active layer and containing Mg as a p-type dopant, the p-type AlGaN layer having a structure in which three or more AlGaN layers having different Al compositions are stacked; a p-type nitride semiconductor layer formed on the p-type AlGaN layer, the p-type nitride semiconductor layer being a semiconductor layer made of a nitride semiconductor containing a p-type dopant; as well as a second multilayer film reflecting mirror, the second multilayer film reflecting mirror being formed on the p-type nitride semiconductor layer and being arranged at a position opposite to the first multilayer film reflecting mirror, wherein, in an Al composition curve indicating a change in the Al composition in the p-type AlGaN layer in a layer thickness direction and a Mg concentration curve indicating a change in the Mg concentration in the p-type AlGaN layer in a layer thickness direction, which are obtained by secondary ion mass spectrometry (SIMS) analysis of the p-type AlGaN layer, When the width range at 50% of the peak of the Al composition curve is defined as the p-type AlGaN layer, and the p-type AlGaN layer is divided into a first region having a layer thickness of 1 / 10 of the p-type AlGaN layer, a second region having a layer thickness of 2 / 5 of the p-type AlGaN layer, and a third region having a layer thickness of 1 / 2 of the p-type AlGaN layer in order from the active layer side in the layer thickness direction, The magnitude relationship between the Al components in each region indicated by the Al composition curve is: the first region < the third region < the second region. The Mg concentration indicated by the Mg concentration curve is less than 3×10 19 atoms / cm 3 , and the relationship between the Mg concentrations in each region is: the first region < the second region < the third region, The average Mg concentration in the second region is 3×10 18 atoms / cm 3 above, and The Mg concentration profile in the second region is configured so that the average value of the absolute value of the slope in the portion on the third region side relative to the center of the second region in the layer thickness direction in the second region is smaller than the average value of the absolute value of the slope in the portion on the first region side.
3. The vertical cavity light emitting element according to claim 1 or 2, wherein: The Mg concentration in the p-type AlGaN layer indicated by the Mg concentration curve is less than 1×10 19 atoms / cm 3 .
4. The vertical cavity light emitting device according to claim 1, wherein: The Mg concentration in the first region indicated by the Mg concentration curve is less than 2×10 18 atoms / cm 3 .
5. The vertical cavity light emitting device according to claim 1, wherein: A difference between an Al composition in the second region and an Al composition in the third region indicated by the Al composition curve is 3% or more and 18% or less.
6. The vertical cavity light emitting device according to claim 1, wherein: The layer thickness of the p-type AlGaN layer is greater than or equal to 8 nm and less than or equal to 15 nm.
7. A method for manufacturing a vertical cavity light emitting element by metal organic chemical vapor deposition (MOCVD), the method comprising: A step of forming a first multilayer film reflecting mirror by alternately growing two semiconductor layers having different refractive indices on a substrate; An n-type nitride semiconductor layer growing step of growing an n-type nitride semiconductor layer on the first multilayer film reflecting mirror while supplying a material gas of an n-type dopant; forming an active layer on the n-type nitride semiconductor layer; a p-type AlGaN layer growing step of growing a p-type AlGaN layer as an AlGaN layer having a p-type conductivity type on the active layer while supplying a material gas of Mg as a p-type dopant; a p-type nitride semiconductor layer growing step, growing a p-type nitride semiconductor layer on the p-type AlGaN layer; as well as forming a second multilayer film reflecting mirror on the p-type nitride semiconductor layer opposite to the first multilayer film reflecting mirror, Wherein, the p-type AlGaN layer growth step comprises: a first growth step of growing a first p-type AlGaN layer by supplying a nitrogen source gas and a Ga material gas in predetermined supply amounts, supplying an Al material gas in a first supply amount, and supplying an Mg material gas in a second supply amount while raising the growth temperature from a first temperature to a second temperature; a second growth step of, after the first growth step, growing a second p-type AlGaN layer while maintaining the supply amounts of the nitrogen source gas, the Ga material gas, the Al material gas, and the Mg material gas used in the first growth step; and A third growth step of growing a third p-type AlGaN layer after the second growth step while supplying the Al material gas at a third supply amount lower than the first supply amount and supplying the Mg material gas at a fourth supply amount lower than the second supply amount.
8. The manufacturing method according to claim 7, further comprising the following steps: After performing the third growth step, the second growth step and the third growth step are performed.
9. The manufacturing method according to claim 8, wherein: The fourth supply amount is less than one tenth of the second supply amount.
10. A method for manufacturing a vertical cavity light emitting element by metal organic chemical vapor deposition (MOCVD), the method comprising: forming a first multilayer film reflecting mirror by alternately growing two semiconductor layers having different refractive indices on a substrate; An n-type nitride semiconductor layer growing step of growing an n-type nitride semiconductor layer on the first multilayer film reflecting mirror while supplying a material gas of an n-type dopant; forming an active layer on the n-type nitride semiconductor layer; a p-type AlGaN layer growing step of growing a p-type AlGaN layer as an AlGaN layer having a p-type conductivity type on the active layer while supplying a material gas of Mg as a p-type dopant; a p-type nitride semiconductor layer growing step, growing a p-type nitride semiconductor layer on the p-type AlGaN layer; as well as forming a second multilayer film reflecting mirror on the p-type nitride semiconductor layer opposite to the first multilayer film reflecting mirror, Wherein, the p-type AlGaN layer growth step comprises: a pretreatment step of supplying a nitrogen source gas at a predetermined supply amount and supplying a Mg material gas at a first supply amount while raising the growth temperature from a first temperature to a second temperature; a first growth step of growing a first p-type AlGaN layer by supplying a Ga material gas at a predetermined supply amount, supplying an Al material gas at a second supply amount, and supplying an Mg material gas at a third supply amount while continuing to supply the nitrogen source gas after the pretreatment step; a second growth step of, after the first growth step, growing a second p-type AlGaN layer while maintaining the supply amounts of the nitrogen source gas, the Ga material gas, the Al material gas, and the Mg material gas used in the first growth step; and A third growth step of growing a third p-type AlGaN layer after the second growth step while supplying the Al material gas at a fourth supply amount lower than the second supply amount and supplying the Mg material gas at a fifth supply amount lower than the third supply amount.
11. The manufacturing method according to claim 8 or 10, wherein: In the p-type AlGaN layer growth step, the atmospheric gas is nitrogen.
12. The manufacturing method according to claim 10, wherein: The third supply amount is equal to or smaller than the first supply amount.
13. The manufacturing method according to claim 10, wherein: The fifth supply amount is less than one tenth of the third supply amount.